Peran Bantuan Langsung Tunai (BLT) dalam Meningkatkan Sistem Jaminan Sosial - Meysa Malika; Saskia A. Hsb; Silmi S; Rosmayanti Rosmayanti; Berlianti Berlianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Direct Cash Transfer (BLT) is one of the Indonesian government's initiatives that aims to provide direct financial support to the community, especially vulnerable groups, in the face of difficult economic conditions. BLT functions as a social safety net to fulfill basic needs and reduce economic burden during times of crisis, such as during the COVID-19 pandemic. Through this research, the author analyzes the role of BLT in strengthening the social security system in Indonesia. This research uses an interview-based qualitative approach and literature study, which provides in-depth insights into the effectiveness of BLT in improving the welfare of vulnerable communities. The results show that BLT not only helps fulfill basic needs, but also increases purchasing power and social resilience. However, improvements in the distribution and supervision of the program are still needed so that its impact can be optimal and sustainable.